A method for synthesizing multi-level porous ZSM-5 molecular sieve nanosheets with controllable b-axis thickness
By using tetrabutylammonium hydroxide as a template agent, the multi-stage pore ZSM-5 molecular sieve nanosheets were synthesized hydrothermal, which solved the problem of failure to synthesize multi-stage pore sheet-like ZSM-5 molecular sieve in the prior art, and achieved structural stability of the molecular sieve Improvement of sexual and mass transfer characteristics.
Patent Information
- Application Number
- CN202310890807.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-07-20
AI Technical Summary
The prior art failed to synthesize multi-stage pore sheet-like ZSM-5 molecular sieve, resulting in rapid deactivation of the catalyst in the catalytic reaction.
Tetrabutylammonium hydroxide was used as the main template agent to synthesize multi-stage pore ZSM-5 molecular sieve nanosheets with micropores and intra-crystal mesopores by hydrothermal method, and the b-axis thickness was adjusted by controlling the crystallization temperature.
Multi-stage pore ZSM-5 molecular sieve nanosheets were successfully synthesized, which significantly shortened the pore length of the molecular sieve, improved the mass transfer characteristics, and improved the structural stability, avoided environmental problems caused by the removal of the molecular sieve skeleton atoms during post-treatment. .
Smart Images

Figure CN117142484B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of molecular sieve synthesis, and in particular relates to a method for synthesizing a multi-level porous ZSM-5 molecular sieve nanosheet with controllable b-axis thickness. Background Art
[0002] ZSM-5 molecular sieve has unique micropores, excellent acid properties and good selectivity, and has shown good catalytic performance in many catalytic reactions, so it is widely used in the petrochemical industry. However, the only micropore of ZSM-5 molecular sieve inevitably limits diffusion, thereby hindering mass transfer and causing rapid deactivation of the catalyst.
[0003] Therefore, in order to reduce the diffusion resistance, the synthesis of multi-level pore molecular sieves and the synthesis of sheet-like ZSM-5 molecular sieves by reducing the thickness of the crystal size have been studied. However, multi-level pore sheet-like ZSM-5 molecular sieves have not yet been synthesized. Summary of the invention
[0004] The purpose of the present invention is to provide a method for synthesizing a multi-level porous ZSM-5 molecular sieve nanosheet with controllable b-axis thickness, which effectively solves the problem that a multi-level porous sheet-like ZSM-5 molecular sieve has not been synthesized at present.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0006] A method for synthesizing a multi-level porous ZSM-5 molecular sieve nanosheet with controllable b-axis thickness comprises the following steps:
[0007] S1. Preparation of seed crystals: Stir a certain amount of tetrapropylammonium hydroxide solution with water, then add a certain amount of tetrabutylammonium hydroxide solution, continue stirring for 4 hours, then drop tetraethyl orthosilicate, stir at room temperature for 6 hours, then put into a hydrothermal crystallization kettle, crystallize at 50-70°C for 60 hours to prepare seed crystals, the molar ratio of each substance in the seed crystals is: SiO 2 :TBAOH:TPAOH:EtOH:H 2 O=1:0.34:0.02:4:11.42;
[0008] S2, mixing a certain amount of tetrapropylammonium hydroxide solution and tetrabutylammonium hydroxide solution, and then mixing with water, tetraethyl orthosilicate and the seed crystal prepared in step S1, and stirring for 2 to 6 hours to obtain a mixed solution I;
[0009] S3, adding a certain amount of aluminum source solution to the mixed solution I, stirring at room temperature overnight to obtain a mixed solution II;
[0010] S4, dissolving a certain amount of ammonium fluoride in water and adding it to the mixed solution II, stirring vigorously, then placing it into a hydrothermal crystallization reactor, crystallizing at 170° C. for 60 h, water cooling and centrifuging, washing with water several times to neutralize, drying and calcining, to prepare a multi-level porous ZSM-5 molecular sieve nanosheet;
[0011] Among all the materials used in preparing the multi-level porous ZSM-5 molecular sieve nanosheets, the proportion of the seed crystal is 30-40wt%, and the molar ratio of the remaining materials is: SiO 2 :xAl 2 O 3 :TBAOH:TPAOH:NH 4 F:H 2 O=1: (0.01~0.02): (0.0325~0.34): (0.0025~0.2): 0.9:70.
[0012] Furthermore, in step S1, the molar ratio of tetrabutylammonium hydroxide to tetrapropylammonium hydroxide is 13-17:1.
[0013] Furthermore, in step S1 and step S2, the concentration of the tetrapropylammonium hydroxide solution is 25 wt %, and the concentration of the tetrabutylammonium hydroxide solution is 40 wt %.
[0014] Furthermore, the aluminum source in step S3 includes one or more of aluminum nitrate, aluminum isopropoxide, aluminum sulfate and aluminum chloride.
[0015] Furthermore, the aluminum source in step S3 is aluminum nitrate and aluminum isopropoxide.
[0016] Furthermore, in step S4, the drying temperature is 80° C., the calcining temperature is 550° C., the calcining time is 4 to 6 hours, and the heating rate during calcining is 1 to 3° C. / min.
[0017] The beneficial technical effects of the present invention are:
[0018] (1) The present invention provides a novel method for in-situ synthesis of multi-level porous ZSM-5 nanosheets with micropores and intercrystalline mesopores by using tetrabutylammonium hydroxide, which is more inexpensive. Compared with the post-treatment method, the novel method avoids a series of environmental problems such as skeleton collapse and generation of acidic and alkaline wastewater caused by removal of skeleton atoms of the molecular sieve during the post-treatment process using acid or alkali, and effectively improves the structural stability of the molecular sieve.
[0019] (2) The multi-level porous ZSM-5 molecular sieve nanosheets synthesized in situ by the method provided by the present invention can significantly shorten the pore length of the molecular sieve due to the short b-axis thickness of the nanosheets and the intracrystalline mesopores, thereby effectively improving the mass transfer characteristics of the molecular sieve pores. In addition, due to the large specific surface area of the molecular sieve, the accessibility of the acid sites is effectively increased.
[0020] (3) The present invention controls the thickness of the b-axis by controlling the crystallization temperature of the ZSM-5 molecular sieve seed synthesis system. The seed crystallization temperature is controlled at 50-70°C. The b-axis thickness of the prepared molecular sieve is between 45-120nm, and the intracrystalline mesopores are about 2.5nm. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is an X-ray diffraction spectrum of the multi-level porous ZSM-5 molecular sieve nanosheet synthesized in Example 1;
[0022] Figure 2 is a scanning electron microscope photograph of the hierarchical ZSM-5 molecular sieve nanosheet synthesized in Example 1;
[0023] Figure 3 is the N of the multi-level pore ZSM-5 molecular sieve nanosheet synthesized in Example 1 2 Adsorption-desorption isotherm mapping;
[0024] Figure 4 is a pore size distribution diagram of the multi-level pore ZSM-5 molecular sieve nanosheet synthesized in Example 1;
[0025] Figure 5 is a scanning electron microscope photograph of the hierarchical ZSM-5 molecular sieve nanosheet synthesized in Example 2;
[0026] Figure 6 is a scanning electron microscope photograph of the hierarchical ZSM-5 molecular sieve nanosheet synthesized in Example 3;
[0027] Figure 7 This is a scanning electron microscope photograph of the molecular sieve synthesized in Comparative Example 1;
[0028] Figure 8 is the N of the molecular sieve synthesized in Comparative Example 1 2 Adsorption-desorption isotherm mapping;
[0029] Fig. 9 is a pore size distribution diagram of the molecular sieve synthesized in Comparative Example 1;
[0030] Fig.10 This is a transmission electron microscope photo of the molecular sieve synthesized in Comparative Example 2;
[0031] Fig.11 is the N of the molecular sieve synthesized in Comparative Example 2 2Adsorption-desorption isotherm mapping;
[0032] Fig.12 This is the pore size distribution diagram of the molecular sieve synthesized in Comparative Example 2. DETAILED DESCRIPTION
[0033] Some of the chemical formulas involved in the present invention are explained as follows:
[0034] SiO 2 -Silica, TBAOH-tetrabutylammonium hydroxide, TPAOH-tetrapropylammonium hydroxide, EtOH-ethanol, Al 2 O 3 -Alumina, NH 4 F-ammonium fluoride.
[0035] The present invention provides a novel method for synthesizing in situ multi-level porous ZSM-5 molecular sieve nanosheets with micropores and intracrystalline mesopores and controllable thickness by using tetrabutylammonium hydroxide as a main template agent for existing sheet molecular sieves. The method has the advantages of simple synthesis steps, easy availability of synthetic raw materials, high crystallinity of the obtained product, uniform size, controllable sheet thickness, large specific surface area, and abundant mesopores.
[0036] A method for synthesizing a multi-level porous ZSM-5 molecular sieve nanosheet with controllable b-axis thickness comprises the following steps:
[0037] S1. Preparation of seed crystals: Stir a certain amount of 25 wt% tetrapropylammonium hydroxide solution with water, then add a certain amount of 40 wt% tetrabutylammonium hydroxide solution, continue stirring, then drop tetraethyl orthosilicate, stir at room temperature for 6 h, then put into a hydrothermal crystallization kettle, crystallize at 50-70° C. for 60 h, and prepare seed crystals.
[0038] The molar ratio of each substance in the seed crystal is: SiO 2 :TBAOH:TPAOH:EtOH:H 2 O=1:0.34:0.02:4:11.42.
[0039] In step S1, the molar ratio of tetrabutylammonium hydroxide to tetrapropylammonium hydroxide is 13-17:1.
[0040] S2. Mix a certain amount of 25 wt % tetrapropylammonium hydroxide solution and 40 wt % tetrabutylammonium hydroxide solution, and then mix with water, tetraethyl orthosilicate and the seed crystal prepared in step S1, and stir to obtain a mixed solution I.
[0041] In step S2, the molar ratio of tetrabutylammonium hydroxide to tetrapropylammonium hydroxide is 13:1.
[0042] S3, adding a certain amount of aluminum source solution to the mixed solution I, stirring overnight at room temperature to obtain a mixed solution II. The aluminum source includes one or more of aluminum nitrate, aluminum isopropoxide, aluminum sulfate and aluminum chloride, preferably aluminum nitrate and aluminum isopropoxide.
[0043] S4, dissolving a certain amount of ammonium fluoride in water and adding it to the mixed solution II, stirring vigorously, then placing it in a hydrothermal crystallization kettle, crystallizing at 170°C for 60 hours, cooling with water and centrifuging, washing with water several times to neutralize, drying at 80°C, and calcining at 550°C for 4-6 hours to prepare a multi-level porous ZSM-5 molecular sieve nanosheet. The heating rate during calcination is 1-3°C / min.
[0044] Among all the materials used in preparing the multi-level porous ZSM-5 molecular sieve nanosheets, the proportion of the seed crystal is 30-40wt%, and the molar ratio of the remaining materials is: SiO 2 :xAl 2 O 3 :TBAOH:TPAOH:NH 4 F:H 2 O=1: (0.01~0.02): (0.0325~0.34): (0.0025~0.2): 0.9:70.
[0045] The present invention is described in detail below with reference to the accompanying drawings, embodiments and comparative examples.
[0046] The XRD analysis of the samples was measured using an X'Pert PRO MPD diffractometer produced by Panalytical of the Netherlands, with a Cu target Kα radiation light source, a tube voltage of 40 kV, a tube current of 40 mA, a scanning step of 0.0167, and diffraction spectra recorded in the range of 2θ 5°-75°.
[0047] The SEM analysis of the samples was carried out on a S-4800 scanning electron microscope produced by Hitachi, Japan, with a magnification of 30-800000 times and an acceleration voltage of 0.5-30 kV.
[0048] TEM analysis of the samples was performed on a JEM-2100UHR transmission electron microscope produced by JEOL, Japan, with an accelerating voltage of 200 kV. The samples were first ultrasonically dispersed in 1 mL of ethanol and then dropped onto a copper grid for testing. The average particle size analysis was performed by counting the sizes of no less than 200 particles in a random area on the image.
[0049] N of sample 2 The adsorption-desorption experiment was carried out on an ASAP 2460 physical adsorption instrument produced by Micromeritics. Before the test, the sample was degassed at 300°C for 6 h, and then its adsorption-desorption isotherm was measured at a low temperature of -196.15°C using high-purity nitrogen as the adsorption medium.
[0050] The pore size analysis of the samples was carried out on an ASAP 2460 physical adsorption instrument produced by Micromeritics.
[0051] All technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art. In addition to the specific methods, devices, and materials used in the examples, those skilled in the art may also use any methods, devices, and materials of the prior art that are similar or equivalent to the methods, devices, and materials in the examples of the present invention to implement the present invention based on their knowledge of the prior art and the description of the present invention.
[0052] The reagents used in the examples of the present invention are all of chemically pure grade.
[0053] Example 1
[0054] (1) Preparation of seed crystals: 0.39 g of 25 wt% tetrapropylammonium hydroxide solution was added to 1.6 g of deionized water and stirred. Then 5.25 g of 40 wt% tetrabutylammonium hydroxide solution was added and stirred vigorously. 5.107 g of tetraethyl orthosilicate was added dropwise to the above solution. The resulting mixed solution was stirred vigorously at room temperature for 6 h, then placed in a hydrothermal crystallization reactor and crystallized at 70° C. for 60 h to prepare seed crystals.
[0055] (2) Synthesis of hierarchical ZSM-5 molecular sieve nanosheets: 0.04 g of 25 wt% tetrapropylammonium hydroxide solution and 0.4 g of 40 wt% tetrabutylammonium hydroxide solution were mixed, and then mixed with the seed crystals prepared in step (1), 2 g of deionized water and 2 g of tetraethyl orthosilicate, and vigorously stirred at room temperature for 2 h to obtain a mixed solution I.
[0056] 4g 0.08mmol / g Al(NO 3 ) 3 9H 2 O solution was added dropwise to the mixed solution I and stirred vigorously at room temperature for 12 h to obtain a mixed solution II. Then 1.01 mol / g NH 4 The F solution was added to the mixed solution II and stirred vigorously. Then, the mixture was placed in a hydrothermal crystallization reactor and crystallized at 170°C for 60 h. After cooling, the mixture was centrifuged and washed until neutral. The above steps were repeated 3 times. The mixture was dried at 80°C overnight and calcined at 550°C for 4 h (heating rate was 2°C / min).
[0057] The multi-level pore ZSM-5 molecular sieve nanosheet samples prepared in Example 1 were subjected to XRD analysis, SEM analysis, and N 2 Adsorption–desorption experiments and pore size analysis.
[0058] X-ray diffraction characterization Figure 1As shown, the XRD spectrum of the multi-level porous ZSM-5 molecular sieve nanosheets showed four characteristic diffraction peaks at 2θ of 8°, 9°, 23°, and 25°, respectively, indicating that it has a typical MFI skeleton structure.
[0059] Scanning electron microscopy characterization Figure 2 As shown, the molecular sieve has a lamellar structure and the b-axis thickness is about 45 nm.
[0060] N 2 Physical adsorption-desorption curves are shown in Figure 3 As shown in the figure, the adsorption isotherm of porous ZSM-5 molecular sieve nanosheets is a typical type IV isotherm. 0 An obvious hysteresis loop appears between 0.8 and 1.0, which is formed by capillary condensation in the mesoporous or macroporous structure, indicating that the multi-level pore ZSM-5 molecular sieve nanosheets have a mesoporous structure.
[0061] Pore size analysis Figure 4 As shown, the multi-level pore ZSM-5 molecular sieve nanosheet contains a mesoporous structure, and the mesopore diameter is relatively concentrated and uniform, about 2.5 nm.
[0062] Example 2
[0063] In this embodiment, compared with embodiment 1, the difference is that the crystallization temperature during the seed crystal preparation process is 60° C. The specific steps are as follows:
[0064] (1) Preparation of seed crystals: 0.39 g of 25 wt% tetrapropylammonium hydroxide solution was added to 1.6 g of deionized water and stirred. Then 5.25 g of 40 wt% tetrabutylammonium hydroxide solution was added and stirred vigorously. 5.107 g of tetraethyl orthosilicate was added dropwise to the above solution. The resulting mixed solution was stirred vigorously at room temperature for 6 h, then placed in a hydrothermal crystallization reactor and crystallized at 60° C. for 60 h to prepare seed crystals.
[0065] (2) Synthesis of hierarchical ZSM-5 molecular sieve nanosheets: 0.04 g of 25 wt% tetrapropylammonium hydroxide solution and 0.4 g of 40 wt% tetrabutylammonium hydroxide solution were mixed, and then mixed with the seed crystals prepared in step (1), 2 g of deionized water and 2 g of tetraethyl orthosilicate, and vigorously stirred at room temperature for 2 h to obtain a mixed solution I.
[0066] 4 g 0.08 mmol / g Al(NO 3 ) 3 9H 2 O solution was added dropwise to the mixed solution I and stirred vigorously at room temperature for 12 h to obtain a mixed solution II. Then 1.01 mol / g NH 4The F solution was added to the mixed solution II and stirred vigorously. Then, the mixture was placed in a hydrothermal crystallization reactor and crystallized at 170°C for 60 h. After cooling, the mixture was centrifuged and washed until neutral. The above steps were repeated 3 times. The mixture was dried at 80°C overnight and calcined at 550°C for 4 h (heating rate was 2°C / min).
[0067] The multi-level pore ZSM-5 molecular sieve nanosheet sample prepared in Example 2 was subjected to SEM analysis. Figure 5 As shown, the molecular sieve has a lamellar structure and the b-axis thickness is about 65 nm.
[0068] Example 3
[0069] In this embodiment, compared with embodiment 1, the difference is that the crystallization temperature during the seed crystal preparation process is 50° C. The specific steps are as follows:
[0070] (1) Preparation of seed crystals: 0.39 g of 25 wt% tetrapropylammonium hydroxide solution was added to 1.6 g of deionized water and stirred. Then 5.25 g of 40 wt% tetrabutylammonium hydroxide solution was added and stirred vigorously. 5.107 g of tetraethyl orthosilicate was added dropwise to the above solution. The resulting mixed solution was stirred vigorously at room temperature for 6 h, and then placed in a hydrothermal crystallization reactor and crystallized at 50° C. for 60 h to prepare seed crystals.
[0071] (2) Synthesis of hierarchical ZSM-5 molecular sieve nanosheets: 0.04 g of 25 wt% tetrapropylammonium hydroxide solution and 0.4 g of 40 wt% tetrabutylammonium hydroxide solution were mixed, and then mixed with the seed crystals prepared in step (1), 2 g of deionized water and 2 g of tetraethyl orthosilicate, and vigorously stirred at room temperature for 2 h to obtain a mixed solution I.
[0072] 4 g 0.08 mmol / g Al(NO 3 ) 3 9H 2 O solution was added dropwise to the mixed solution I and stirred vigorously at room temperature for 12 h to obtain a mixed solution II. Then 1.01 mol / g NH 4 The F solution was added to the mixed solution II and stirred vigorously. Then, the mixture was placed in a hydrothermal crystallization reactor and crystallized at 170°C for 60 h. After cooling, the mixture was centrifuged and washed until neutral. The above steps were repeated 3 times. The mixture was dried at 80°C overnight and calcined at 550°C for 4 h (heating rate was 2°C / min).
[0073] The multi-level pore ZSM-5 molecular sieve nanosheet sample prepared in Example 3 was subjected to SEM analysis. Figure 6 As shown, the molecular sieve has a lamellar structure and the b-axis thickness is about 125 nm.
[0074] Comparative Example 1
[0075] In this comparative example, ammonium fluoride was not added during the synthesis process, and the specific steps were as follows:
[0076] 0.39 g of 25 wt% tetrapropylammonium hydroxide solution was added to 1.6 g of deionized water, and then 5.25 g of 40 wt% tetrabutylammonium hydroxide solution was added and stirred vigorously. 5.107 g of tetraethyl orthosilicate was added dropwise to the above solution. The resulting mixed solution was stirred vigorously at room temperature for 6 h. Then 4 g of 0.08 mmol / g Al(NO 3 ) 3 9H 2 O solution was added dropwise to the above solution, then vigorously stirred at room temperature for 12 h, placed in a hydrothermal crystallization kettle, crystallized at 170 ° C for 60 h, centrifuged and washed to neutral after cooling, the above steps were repeated 3 times, dried at 80 ° C overnight, and calcined at 550 ° C for 4 h (heating rate of 2 ° C / min).
[0077] The molecular sieve samples prepared in Comparative Example 1 were subjected to SEM analysis, N 2 Adsorption-desorption experiment and pore size analysis. Its scanning electron microscopy characterization is as follows Figure 7 As shown, the molecular sieve is a kind of agglomerated stacking structure. 2 Physical adsorption-desorption curves are shown in Figure 8 As shown in Figure 1, the adsorption isotherm of the molecular sieve is a typical type I isotherm, indicating that the molecular sieve directly crystallized without adding ammonium fluoride is a microporous material. Fig. 9 As shown, the molecular sieve contains substantially no mesoporous structure.
[0078] Comparative Example 2
[0079] In this comparative example, only tetrapropylammonium hydroxide is used as a template, and the specific steps are as follows:
[0080] (1) Preparation of seed crystals: 6.85 g of 25 wt% tetrapropylammonium hydroxide solution was added to 1.6 g of deionized water and stirred. 5.107 g of tetraethyl orthosilicate was added dropwise to the above solution. The resulting mixed solution was vigorously stirred at room temperature for 6 h, then placed in a hydrothermal crystallization reactor and crystallized at 70° C. for 60 h to prepare seed crystals.
[0081] (2) Synthesis of hierarchical pore flaky molecular sieve: 1.86 g of 25 wt% tetrapropylammonium hydroxide solution and 0.61 g of tetrapropylammonium bromide were mixed, and then mixed with the seed crystals prepared in step (1), 2 g of deionized water and 2 g of tetraethyl orthosilicate, and stirred vigorously at room temperature for 2 h to obtain a mixed solution I.
[0082] 4 g 0.08 mmol / g Al(NO 3 ) 3 9H 2O solution was added dropwise to the mixed solution I and stirred vigorously at room temperature for 12 h to obtain a mixed solution II. Then 1.01 mol / g NH 4 The F solution was added to the mixed solution II and stirred vigorously. Then, the mixture was placed in a hydrothermal crystallization reactor and crystallized at 170°C for 60 h. After cooling, the mixture was centrifuged and washed until neutral. The above steps were repeated 3 times. The mixture was dried at 80°C overnight and calcined at 550°C for 4 h (heating rate was 2°C / min).
[0083] The molecular sieve samples prepared in Comparative Example 2 were subjected to TEM analysis, N 2 Adsorption-desorption experiment and pore size analysis. Fig.10 As shown, the molecular sieve is a sheet structure with a b-axis thickness of about 35nm. 2 Physical adsorption-desorption curves are shown in Fig.11 As shown in Figure 1, the adsorption isotherm of the molecular sieve is a typical type I isotherm, indicating that the molecular sieve with only TPAOH as the template is a microporous material. Fig.12 As shown, the molecular sieve contains substantially no mesoporous structure.
[0084] The molecular sieve pore structures of the samples prepared in Examples 1-3 and Comparative Examples 1-2 were measured using an ASAP 2460 physical adsorption instrument produced by Micromeritics, and the results are shown in Table 1: as the b-axis thickness of the samples in Examples 1-3 increases, the specific surface area and external specific surface area of the molecular sieves decrease; the sample in Comparative Example 1 has a larger specific surface area due to its stacking structure, but the stacking structure will cause some diffusion paths to become longer, affecting the diffusion effect; the sample in Comparative Example 2 is a flaky molecular sieve obtained using only tetrapropylammonium hydroxide as a template, and the sample in Comparative Example 2 also has a larger specific surface area and external specific surface area, but a smaller mesopore volume.
[0085] Table 1 Molecular sieve pore structure parameters of Examples 1-3 and Comparative Examples 1-2
[0086]
[0087] The structures of the samples prepared in Examples 1-3 and Comparative Examples 1-2 are shown in Table 2: The samples in Examples 1-3 all have micropores and intracrystalline mesopores, and are monolithic structures, which greatly improve the diffusion performance. The molecular sieve in Comparative Example 1 is an agglomerated stacking structure and has no intracrystalline mesopores. The molecular sieve in Comparative Example 2 is flaky but has no mesoporous structure.
[0088] Table 2 Structural data of Examples 1-3 and Comparative Examples 1-2
[0089] sample B-axis thickness Morphology Are there intracrystalline mesopores? Example 1 45nm Monolithic Layer have Example 2 65nm Monolithic Layer have Example 3 125nm Monolithic Layer have Comparative Example 1 —— Agglomeration Stacking Almost no Comparative Example 2 40nm Monolithic Layer Almost no
[0090] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A method for synthesizing a multi-level porous ZSM-5 molecular sieve nanosheet having intracrystalline mesopores and controllable b-axis thickness, characterized in that: The following steps are involved: S1. Preparation of seed crystals: Stir a certain amount of tetrapropylammonium hydroxide solution with water, then add a certain amount of tetrabutylammonium hydroxide solution, continue stirring, then drop tetraethyl orthosilicate, stir at room temperature for 6 hours, then put into a hydrothermal crystallization kettle, crystallize at 50-70° C. for 60 hours to prepare seed crystals, wherein the molar ratio of each substance in the seed crystals is: SiO2:TBAOH:TPAOH:EtOH:H2O=1:0.34:0.02:4:11.42; S2, mixing a certain amount of tetrapropylammonium hydroxide solution and tetrabutylammonium hydroxide solution, and then mixing with water, tetraethyl orthosilicate and the seed crystal prepared in step S1, and stirring to obtain a mixed solution I; S3, adding a certain amount of aluminum source solution to the mixed solution I, stirring at room temperature overnight to obtain a mixed solution II; S4, dissolving a certain amount of ammonium fluoride in water and adding it to the mixed solution II, stirring vigorously, then loading it into a hydrothermal crystallization kettle, crystallizing at 170°C for 60h, water cooling and centrifugal separation, washing with water several times to neutralize, drying and calcining, the drying temperature is 80°C, the calcining temperature is 550°C, the calcining time is 4-6h, and the heating rate during calcination is 1-3°C / min, to prepare a multi-level porous ZSM-5 molecular sieve nanosheet with intracrystalline mesopores; Among all the substances used in preparing the multi-level porous ZSM-5 molecular sieve nanosheets, the proportion of the seed crystal is 30-40wt%, and the molar ratio of the remaining substances is: SiO2:xAl2O3:TBAOH:TPAOH:NH4F:H2O=1:(0.01-0.02):(0.0325-0.34):(0.0025-0.2):0.9:70; In step S1, the molar ratio of tetrabutylammonium hydroxide to tetrapropylammonium hydroxide is 13-17:1; In step S1 and step S2, the concentration of the tetrapropylammonium hydroxide solution is 25wt%, and the concentration of the tetrabutylammonium hydroxide solution is 40wt%; The aluminum source in step S3 is aluminum nitrate and aluminum isopropoxide.